Criminalising cannabis in South Africa: a history and post-Prince discussion - Weihrauch, Ronja (Department of Private Law, 2021)
This thesis circles around the history of the criminalisation of cannabis as well as its decriminalisation around 100 years later. While dagga was cultivated and used by the indigenous tribes long before the first settlers arrived and even remained a legal substance during the colonial period, with the implementation of the first national legislation in 1922, the long history of harsh punishments began. Relating the harsh legislation on dagga to its estimated risks, I ultimately confirm dagga to be the black sheep among drugs, having experienced a racial prohibition. In September 2018, the Constitutional Court partially decriminalised dagga, due to the inconsistency of certain regulations prohibiting the use, possession, and cultivation of dagga with the right to privacy as referenced from section 14 of the Constitution. Emphasising the significant and practical impact of this judgement, possibly positive effects of the decision as well as the newly introduced Cannabis for Private Purposes Bill on the desperately overwhelmed criminal justice system are examined. Concluding, I find that the discourse around dagga most certainly is far from complete but that we have to continue conducting it. Because if history teaches us one thing it is that dagga is here to stay.